Recursive Formula Explained: Boost your Math IQ


Deepak Prasad

Mathematics

What is a Recursive Formula?

In mathematics, sequences often follow patterns. Some sequences can be expressed directly in terms of their position, while others depend on previous terms. A recursive formula belongs to the latter category. Instead of calculating the nth term directly, a recursive formula determines each term of a sequence based on one or more preceding terms. Consider the arithmetic sequence, where each term is obtained by adding a fixed number, known as the common difference, to the previous term. The recursive formula for such a sequence is: \[ a_n = a_{n-1} + d \] Where \(a_n\) represents the nth term, \(a_{n-1}\) is the (n-1)th or previous term, and \(d\) is the common difference. This formula tells us that to get any term in the sequence (except the first one), we simply add the common difference \(d\) to the preceding term.

 

Importance of Recursive Thinking in Mathematics

Recursive thinking is foundational in both mathematics and computer science. It's a method where problems are broken down into simpler versions of themselves. This approach reduces complex challenges to their base components, making them easier to address. Take, for instance, the factorial function. The factorial of a positive integer \(n\), denoted as \(n!\), is the product of all positive integers less than or equal to \(n\). This function can be defined recursively: \[ n! = n \times (n-1)! \] With a base case: \[ 0! = 1 \]
This means that the factorial of any number \(n\) is \(n\) times the factorial of \(n-1\), and this process continues recursively until we reach the factorial of 0, which is defined to be 1.

 

Basics of Sequences

A \(sequence\) is an ordered list of numbers. Each number in a sequence is often referred to as a \(term\). Sequences can be finite, such as the sequence of the first ten positive integers: \(1, 2, 3, ... , 10\), or infinite, like the sequence of all positive integers: \(1, 2, 3, ... \). \[ \] The \(nth term\) of a sequence is often denoted \(a_n\). For instance, in the sequence of squares \(1, 4, 9, 16, ...\), the term \(a_3\) would be 9 since it's the third term.

There are primarily two ways to define sequences: using explicit formulas or recursive formulas.

Explicit Formulas:

An explicit formula describes the nth term of a sequence in relation to \(n\) itself. No previous terms are needed. For instance, for the sequence of squares mentioned earlier, the explicit formula is \(a_n = n^2\). Here, to find the 5th term, we'd calculate \(5^2 = 25\). \[ \]

Recursive Formulas:

On the other hand, a recursive formula defines the terms of a sequence using one or more of its preceding terms. This means to determine a certain term; you need to know one or more previous terms. For example, if we have a sequence where each term is the sum of the two preceding terms, a possible recursive formula could be \(a_n = a_{n-1} + a_{n-2}\) (This is the definition for the Fibonacci sequence).

Here's a simple example:

Consider the sequence where each term is 2 more than the previous term, starting at 3. The sequence goes: \(3, 5, 7, 9, ...\). The recursive formula for this sequence is: \(a_1 = 3\) (This sets the first term) And for n > 1: \(a_n = a_{n-1} + 2\).

 

Simple Recursive Formulas

Recursion in mathematics refers to the process of defining something in terms of itself. Recursive formulas provide a way to compute terms of a sequence by referring to previous terms in the same sequence. Let's delve into two types of recursive formulas: linear recursion and quadratic recursion.

1. Linear Recursion (Arithmetic Sequences)

Arithmetic sequences are a classic example of linear recursion. In such sequences, each term is determined by adding (or subtracting) a fixed number to the previous term. This fixed number is called the "common difference", denoted as \( d \).

General Recursive Formula for Arithmetic Sequences:

\[ a_n = a_{n-1} + d \]

Example

Consider the arithmetic sequence that starts with 5 and has a common difference of 3: \( 5, 8, 11, 14, ... \).

The recursive formula for this sequence is:

\[ a_1 = 5 \] For \( n > 1 \): \[ a_n = a_{n-1} + 3 \]

2. Quadratic Recursion (Geometric Sequences)

Now, let's discuss geometric sequences, which represent quadratic recursion. In these sequences, each term is found by multiplying the previous term by a fixed non-zero number called the "common ratio", denoted as \( r \).

General Recursive Formula for Geometric Sequences:

\[ a_n = a_{n-1} \times r \]
Consider the geometric sequence that begins with 2 and has a common ratio of 3: \( 2, 6, 18, 54, ... \).

The recursive formula for this sequence is:

\[ a_1 = 2 \] For \( n > 1 \): \[ a_n = a_{n-1} \times 3 \]

In both linear and quadratic recursion, the idea is to express the nth term in terms of previous terms. This recursive nature gives us a methodical way to generate sequences, making it easier to understand and work with them, especially for new students.

 

Working with Recursive Formulas

Recursive formulas are pivotal tools in mathematics for defining sequences. To effectively work with them, one must understand how to find the subsequent term and, in some cases, determine a term without necessarily knowing all the previous ones. Let's explore this further.

1. Finding the Next Term

Given a recursive formula and one or more initial terms, we can easily compute the subsequent terms of the sequence.

Example 1 (Arithmetic Sequence):

Given the arithmetic sequence starting with 4 and with a common difference \( d = 3 \): \[ a_1 = 4 \] \[ a_n = a_{n-1} + 3 \]

From this:

\[ a_2 = a_1 + 3 = 7 \] \[ a_3 = a_2 + 3 = 10 \] ... and so on.

Example 2 (Geometric Sequence):

For the geometric sequence starting with 5 and with a common ratio \( r = 2 \): \[ a_1 = 5 \] \[ a_n = a_{n-1} \times 2 \] From this: \[ a_2 = a_1 \times 2 = 10 \] \[ a_3 = a_2 \times 2 = 20 \] ... and so forth.

2. Calculating a Specific Term Without Knowing All Previous Terms

While recursive formulas usually require knowledge of preceding terms, for some specific sequences like arithmetic or geometric, there are explicit formulas to calculate any term directly.

Arithmetic Sequence:

For the general formula \( a_n = a_1 + (n-1) \times d \), where \( d \) is the common difference.
For the sequence with \( a_1 = 4 \) and \( d = 3 \): To find \( a_5 \) directly: \[ a_5 = 4 + 4 \times 3 = 16 \]

Geometric Sequence:

The general formula is \( a_n = a_1 \times r^{(n-1)} \), where \( r \) is the common ratio.
For the sequence with \( a_1 = 5 \) and \( r = 2 \): To determine \( a_4 \) without the prior terms: \[ a_4 = 5 \times 2^3 = 40 \]

 

Common Examples in Mathematics

1. Fibonacci Sequence

The Fibonacci sequence is a famous sequence where each term is the sum of the two preceding terms. Mathematically, the Fibonacci sequence is represented as: \[ F_0 = 0 \] \[ F_1 = 1 \] \[ F_n = F_{n-1} + F_{n-2} \]
Starting with \( F_0 \) and \( F_1 \), the first few terms of the Fibonacci sequence are: \[ F_0 = 0, F_1 = 1, F_2 = 1, F_3 = 2, F_4 = 3, F_5 = 5, \dots \]

2. Factorials

Factorials are a fundamental concept in mathematics, especially in combinatorics. The factorial of a non-negative integer \( n \), denoted as \( n! \), is the product of all positive integers less than or equal to \( n \). Recursively, factorials are defined as: \[ n! = n \times (n-1)! \] With the base case: \[ 0! = 1 \]
For \( n = 4 \): \[ 4! = 4 \times 3! = 4 \times 3 \times 2! = 4 \times 3 \times 2 \times 1! = 4 \times 3 \times 2 \times 1 = 24 \]

3. Pascal’s Triangle

Pascal's Triangle is a triangular array of binomial coefficients. Each number in Pascal's Triangle is the sum of the two numbers directly above it.

The \( n^{th} \) row and \( k^{th} \) column of Pascal's Triangle (starting both row and column count from 0) is denoted by \( \binom{n}{k} \) and represents the number of ways to choose \( k \) elements from \( n \) without repetition. This value is calculated as: \[ \binom{n}{k} = \frac{n!}{k! \times (n-k)!} \] In terms of Pascal's Triangle, this is represented as: \[ \binom{n}{k} = \binom{n-1}{k-1} + \binom{n-1}{k} \]
To find the 4th row (remember, we start counting from 0) of Pascal's Triangle: \[ \binom{4}{0}, \binom{4}{1}, \binom{4}{2}, \binom{4}{3}, \binom{4}{4} \] This becomes: \[ 1, 4, 6, 4, 1 \]

 

Benefits and Limitations of Recursive Formulas

1. Advantages of Using Recursive Formulas

- \(Simplicity\): Recursive formulas can be simpler and more intuitive to define, especially when describing sequences or series where each term is based on one or more previous terms. For instance, the Fibonacci sequence \( F_n = F_{n-1} + F_{n-2} \) is easily understood as each number being the sum of the two preceding numbers.
- \(Elegant Problem Solving\): Recursive techniques can turn complex problems into simpler ones, making them more tractable. Consider the task of calculating the factorial of a number \( n! \). Instead of performing \( n \) multiplications, we can express \( n! \) as \( n \times (n-1)! \), which reduces the problem size by one at each step.
- \(Foundation for Algorithms\): In computer science, recursive algorithms can be a more direct representation of a problem. They form the basis for many essential algorithms, like the merge sort or quick sort in sorting algorithms.

2. Challenges and Drawbacks

  • Efficiency Concerns: Recursive formulas can sometimes be less efficient than their iterative counterparts, especially when they involve repeated calculations. For example, using the naive recursive approach for the Fibonacci sequence can result in exponential time complexity.
  • Stack Overflow: In computing, a deep recursion can lead to a stack overflow. This is because each recursive call uses space on the call stack. If the stack space gets exhausted, it can cause the program to crash.
  • Base Case Requirement: Every recursive formula or function requires a base case to prevent infinite recursion. Sometimes, defining this base case can be non-trivial.
  • Cognitive Load: While recursion can simplify problems, it can sometimes be harder to follow or understand compared to iterative solutions. It might demand a higher cognitive load for some students or professionals to visualize or trace recursive processes.

Examples in Context:

1. Consider the recursive formula for finding the sum of the first \( n \) natural numbers: \( S(n) = n + S(n-1) \) with a base case \( S(1) = 1 \). This formula breaks down the problem into a smaller version of itself. However, an iterative approach using the formula \( S(n) = \frac{n \times (n+1)}{2} \) might be more efficient for large values of \( n \).
2. A classic recursive problem in computer science is the "Tower of Hanoi". While the recursive solution provides an elegant approach to the problem, an iterative solution might be less intuitive but can be more space-efficient in some scenarios.

 

Converting between Recursive and Explicit Formulas

1. From Recursive to Explicit Formulas

When you have a recursive formula and want to derive its explicit (or closed-form) counterpart, the goal is to express the th term without reference to any preceding terms.

Suppose you have the recursive arithmetic sequence: \( a_n = a_{n-1} + d \) where \( d \) is the common difference and \( a_1 \) is the first term.

To derive the explicit formula:

1. Sum up the differences. After \( n-1 \) steps, the total difference added will be \( d(n-1) \).
2. Add this total to the first term: \( a_n = a_1 + d(n-1) \).
Thus, the explicit formula is \( a_n = a_1 + d(n-1) \).

2. From Explicit to Recursive Formulas

For this conversion, the goal is to express the \(n\)th term in terms of one or more of its preceding terms.
Let's reverse the previous scenario. Given the explicit arithmetic formula \( a_n = a_1 + d(n-1) \).

To derive the recursive formula:

1. Express \( a_n \) in terms of \( a_{n-1} \).
2. \( a_n = a_{n-1} + d \).

This is the recursive formula for an arithmetic sequence.

3. More Complex Scenarios: Using Characteristic Equations

The conversion of a recursive sequence to an explicit formula using the characteristic equation associated with linear homogeneous recursions. This method is particularly useful for sequences like the Fibonacci series.

Consider the Fibonacci sequence:

\[ F(n) = F(n-1) + F(n-2) \] with initial conditions: \( F(0) = 0 \) and \( F(1) = 1 \).
The characteristic equation is derived by substituting the terms of the sequence with powers of \( r \):
\[ r^n = r^{n-1} + r^{n-2} \] Which simplifies to: \[ r^2 = r + 1 \]
Solving this quadratic gives us: \[ r_1 = \frac{1 + \sqrt{5}}{2} \quad \text{and} \quad r_2 = \frac{1 - \sqrt{5}}{2} \]

These roots (also known as the golden ratio and its inverse) can be used to generate the general solution:

\[ F(n) = A \left( \frac{1 + \sqrt{5}}{2} \right)^n + B \left( \frac{1 - \sqrt{5}}{2} \right)^n \]
Using our initial conditions, \( F(0) = 0 \) and \( F(1) = 1 \), we can solve for \( A \) and \( B \) to get the explicit formula:
\[ F(n) = \frac{1}{\sqrt{5}} \left( \left( \frac{1 + \sqrt{5}}{2} \right)^n - \left( \frac{1 - \sqrt{5}}{2} \right)^n \right) \]

 

Advanced Recursive Formulas

1. Multi-level Recursion

Unlike simple recursion which references only one previous term, multi-level recursion references multiple prior terms. This deepens the dependency chain.

Consider the Fibonacci sequence. It's defined as:

\[ F(n) = F(n-1) + F(n-2) \] with base cases: \( F(0) = 0 \) and \( F(1) = 1 \).
Here, the \( n \)th term is defined in terms of the two preceding terms. This is a classic example of a second-order (or two-level) recursion.

2. Recursions with More Complex Base Cases

Sometimes the base cases themselves have intricate definitions, making the recursive process more challenging to understand and implement

Consider a sequence \( a_n \) defined as: \[ a_n = 2a_{n-1} - 3a_{n-2} + 4a_{n-3} \] with base cases: \( a_0 = 2 \), \( a_1 = -1 \), and \( a_2 = 3 \).
Here, to calculate the fourth term \( a_3 \), one would need the three previous terms. It also demonstrates how base cases can be both positive and negative, adding layers of complexity.

3. Generating Functions

A generating function is a way to encapsulate an entire sequence within a single function. Specifically, for a sequence \{a_n\}, its generating function \(G(x)\) is defined as: \[ G(x) = a_0 + a_1x + a_2x^2 + a_3x^3 + \ldots \]

Example: Fibonacci Sequence

The Fibonacci sequence is a famous sequence defined by: \[ F(n) = F(n-1) + F(n-2) \] with \( F(0) = 0 \) and \( F(1) = 1 \).

Let's find the generating function for the Fibonacci sequence.

Let \( F(x) \) be the generating function for the Fibonacci sequence: \[ F(x) = F(0) + F(1)x + F(2)x^2 + F(3)x^3 + \ldots \]

Using the recursive relation:

\[ F(n)x^n = F(n-1)x^n + F(n-2)x^{n+1} \]
Summing over all \( n \): \[ F(x) = x + xF(x) + x^2F(x) \] Rearranging: \[ F(x) = \frac{x}{1-x-x^2} \]

This is the generating function for the Fibonacci sequence.

 

Sample Problems on Recursive Formula

Sample Problem 1: Arithmetic Sequence

Problem:

The first term of an arithmetic sequence is \( a_1 = 5 \). The recursive formula given is \( a_n = a_{n-1} + 3 \). Find the fourth term.

Solution:

Using the recursive formula: \[ a_1 = 5 \] \[ a_2 = a_1 + 3 = 5 + 3 = 8 \] \[ a_3 = a_2 + 3 = 8 + 3 = 11 \] \[ a_4 = a_3 + 3 = 11 + 3 = 14 \] Hence, the fourth term \( a_4 \) is 14.

Sample Problem 2: Geometric Sequence

Problem:

The first term of a geometric sequence is \( b_1 = 2 \). The recursive formula given is \( b_n = 2b_{n-1} \). Find the third term.

Solution:

Using the recursive formula: \[ b_1 = 2 \] \[ b_2 = 2b_1 = 2(2) = 4 \] \[ b_3 = 2b_2 = 2(4) = 8 \] Thus, the third term \( b_3 \) is 8.

Sample Problem 3: Fibonacci Sequence

Problem:

The Fibonacci sequence is defined as \( F(n) = F(n-1) + F(n-2) \) with \( F(1) = 1 \) and \( F(2) = 1 \). Find \( F(5) \).

Solution:

Using the recursive formula: \[ F(1) = 1 \] \[ F(2) = 1 \] \[ F(3) = F(2) + F(1) = 1 + 1 = 2 \] \[ F(4) = F(3) + F(2) = 2 + 1 = 3 \] \[ F(5) = F(4) + F(3) = 3 + 2 = 5 \] Hence, the fifth term \( F(5) \) is 5.

Sample Problem 4: Recursive Factorials

Problem:

The factorial of a number is defined recursively as \( n! = n(n-1)! \) with \( 0! = 1 \). Find \( 4! \).

Solution:

Using the recursive formula: \[ 0! = 1 \] \[ 1! = 1 \times 0! = 1 \] \[ 2! = 2 \times 1! = 2 \] \[ 3! = 3 \times 2! = 6 \] \[ 4! = 4 \times 3! = 24 \] Thus, \( 4! \) is 24.

 

Conclusion

Understanding and mastering recursive formulas is pivotal for anyone venturing into mathematics, computer science, or any field that demands analytical problem-solving. Not only does recursion simplify complex problems, but it also offers a structured approach to tackle them. The beauty of recursion lies in its inherent nature of self-replication, where large problems are broken down into smaller, more manageable sub-problems. Moreover, the ability to convert between recursive and explicit formulas further accentuates the flexibility and adaptability of this concept.

You can read more at Recursive Function

 

Views: 5

Deepak Prasad

He is the founder of GoLinuxCloud and brings over a decade of expertise in Linux, Python, Go, Laravel, DevOps, Kubernetes, Git, Shell scripting, OpenShift, AWS, Networking, and Security. With extensive experience, he excels in various domains, from development to DevOps, Networking, and Security, ensuring robust and efficient solutions for diverse projects. You can reach out to him on his LinkedIn profile or join on Facebook page.

Can't find what you're searching for? Let us assist you.

Enter your query below, and we'll provide instant results tailored to your needs.

If my articles on GoLinuxCloud has helped you, kindly consider buying me a coffee as a token of appreciation.

Buy GoLinuxCloud a Coffee

For any other feedbacks or questions you can send mail to admin@golinuxcloud.com

Thank You for your support!!

Leave a Comment


We try to offer easy-to-follow guides and tips on various topics such as Linux, Cloud Computing, Programming Languages, Ethical Hacking and much more.

Programming Languages

JavaScript

Python

Golang

Node.js

Java

Laravel